A model of the international steam coal market (COALMOD-World) - Franziska Holz; Clemens Haftendorn; Roman Mendelevitch; Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Coal is at the core of the debate about climate change mitigation policies, yet the international market for it is not well represented in most energy models. This paper presents the COALMOD framework which is a model of the international steam coal market that can be readily used to explore implications of climate policies, but also to analyze market structure or to investigate issue of supply security. It features a detailed representation of both domestic and international steam coal supply, based on endogenously calculated Cost, Insurance, Fright (CIF) costs, and prices that take into account additional rents. It features endogenous investment into production, land transport, and export capacity, as well as an endogenous mechanism assessing production cost increase due to resource depletion. We provide a detailed model and data description and illustrate the features of the model by analyzing to scenarios derived from the IEA World Energy Outlook (New Policies and 450 ppm scenario), highlighting the functionalities of the model.
Keywords: C72; C69; L11; L71; Q41; 330; Future coal markets; Partial equilibrium modeling; International trade